KARAKTERISTIK SIFATFISIK SEMEN DOMBA ST. CROIX - Feradis Feradis (State Islamic University of Sultan Syarif Kasim Riau, 2007)
The objectives of this research are to determine the characteristichs of St. Croix ram semen instead to semen cryopreservation.Results of the research revealed that the mean sperm volume is 1.54 ± OA1 mI, colour is crem, pH is 6.8 ± 0.01, concentration is 3.785 ± 343.79 million/ml, mean sperm motility is 81.67 ± 2.58%, live sperm cpunt is 89 ± 2.37%, apical rich (fAU) is 94 ±1.27%, intact plasma membrane (MPU) is 86.33 ±2.34% and abnormal sperm is 8.33 ±1.37%.Itis concluded that St. Croix ram semen have good quality and may be used for semen cryopreservation.